KNOWLEDGE OF SEXUALLY TRANSMITTED INFECTIONS AND RISKY PRACTICES AMONG FEMALE ALCOHOL BREWERS AND SELLERS IN IBADAN NORTH EAST LOCAL GOVERNMENT AREA (2013)
Studies have shown that there is an increasing prevalence of high-risk sexual practices among alcohol users which can lead to Sexually Transmitted Infections (STIs). In Nigeria, knowledge relating to STIs, alcohol use and sexual practices among female alcohol handlers is sparse. The study was therefore aimed at assessing the knowledge of STIs, sexual practices and alcohol use among this category of women in Ibadan North-East Local Government Area (LGA). The study was a cross-sectional survey of female alcohol brewers and sellers in Ibadan North-East LGA. All the consenting 374 females aged 20 years and above, identified through leaders of the local brewers and bar owners associations were interviewed. A validated semi-structured questionnaire which included a 21-point knowledge scale was used to measure respondents’ STI knowledge. Risky practices assessed included possession of multiple sexual partners, inconsistent condom use and alcohol use before sexual intercourse. Data were analyzed using descriptive statistics, Chi-square test and ANOVA at 5% level of significance. Respondents’ mean age was 36.0 ± 9.1years and 81.3% had formal education. Forty-five per cent were married, 16.3% single, 14.2% separated and others were cohabiting (12.0%), divorced (7.8%) and widowed (5.1%). Sellers of industrially brewed alcoholic drinks comprised 44.4% while 55.6% brewed and sold traditional alcoholic beverages. The mean number of hours spent selling alcohol was 10.9 ± 3.4 hours. Mean STI knowledge score was lower in respondents who brewed and sold traditionally brewed alcoholic beverages (8.6 ± 2.5) while the score for those that sold industrial alcoholic beverages was 8.7 ± 2.7 with no significant difference. Respondents who were single had the highest STI knowledge score of 10.3±2.2 while the mean scores among married, widowed, cohabiting, separated and divorced respondents were 8.6 ± 2.5, 8.5 ± 1.9, 8.4 ± 2.7, 7.7 ± 2.7 and 7.7 ± 2.2 respectively. Overall mean STI knowledge score of respondents was 10.4 ± 3.4. Majority of the respondents (81.3%) had ever consumed alcohol out of which 70.4% still consumed regularly. Reasons for alcohol consumption included: for treatment of ailments (31.1%), pleasure and relaxation (26.5%), social acceptance (25.3%), as an aphrodisiac (4.7%). Risky practices reported included inconsistent condom use (58.7%) and having more than one sexual partner (53.0%). Only 12.3% had ever become intoxicated. Many married respondents (48.9%) and those aged 30-39 years (42.2%) engaged in the aforementioned risky practices. More married respondents engaged in at least a risky practice compared with the separated (15.9%), cohabiting (14.8%), divorced (7.8%), single (7.4%) and widowed (5.2%) respondents. The alcohol handlers used alcohol and indulge in risky sexual practices. Health education interventions such as public enlightenment and peer education are needed to address these challenges. The Government can also provide small micro-finance schemes as a means of alternative self reliance avenues among young females.